Survey of Minas frescal cheese from Southwest Minas Gerais for virulence factors and antimicrobial resistance in Escherichia coli isolates - Okura, Mõnica Hitomi; Marin, José Moacir (Universidade Federal de Santa Maria, 2014)
The soft cheese Minas frescal is one of the most popular cheese in Brazil, which is typically manufactured in small dairy farms under unsatisfactory hygiene conditions. To assess the risk involved in consumption of this cheese, virulence markers were investigated in 330 Escherichia coli strains isolated from 30 Minas frescal cheeses inspected by official government agency (SIF - serviço de inspeção federal), from 50 cheeses not inspected by SIF and 31 cheeses not inspected by SIF with spice added, all of them collected in the southwest of Minas Gerais State. The E. coli isolates were screened for the presence of Shiga toxin-encoding (stx 1 and stx 2), intimin (eae) genes and for the presence of (pap, sfa, afa) genes related to adhesion in epithelial cells. The only gene detected by PCR was the sfa gene at one isolate. The strains were also screened for resistance to 9 antimicrobial drugs. Predominant resistance was to cephalothin, tetracycline and streptomycin. Multidrug resistance was found among isolates from cheese with SIF (16.6%), cheese without SIF (8.0%) and cheese without SIF with spice added (30.0%) what is a reason for concern due to the high consumption of raw milk cheese by the Brazilian population.

O queijo Minas frescal é um dos queijos mais populares no Brasil, ele é tipicamente manufaturado em pequenas fazendas de leite, em condições higiênicas insatisfatórias. Para verificar o risco envolvido no consumo deste queijo, marcadores de virulência foram investigados em 330 cepas de isoladas de 30 queijos Minas frescal, inspecionados pela agencia governamental oficial (SIF- serviço de inspeção federal), de 50 queijos não inspecionados pelo SIF e de 31 queijos não inspecionados pelo SIF e com condimentos adicionados. Todos eles foram coletados na região sudeste do Estado de Minas Gerais. As cepas de E. coli foram examinadas para a presença de genes codificadores de Shiga toxina (stx1 e stx 2), gene da intimina (eae) e também para a presença dos genes (pap, sfa, afa) relacionados com a adesão em células epiteliais. O único gene detectado por PCR foi sfa em um isolado. As cepas também foram examinadas para a resistência a nove fármacos antimicrobianos. As resistências predominantemente detectadas foram para cefalotina, tetraciclina e estreptomicina. A resistência a múltiplas drogas identificadas entre as cepas de E. coli, provenientes de queijo com SIF (16,6%), queijo sem SIF (8,0%) e queijo sem SIF com condimentos adicionados (30,0%), o que representa um motivo de preocupação, devido ao elevado consumo pela população Brasileira de queijos feitos de leite não pasterurizado.
Avaliação em queijos Minas frescal provenientes do Sudoeste de Minas Gerais da presença de fatores de virulência e resistência antimicrobiana em isolados de Escherichia coli
Keywords: Escherichia coli; queijo; STEC; ExPEC; resistência antimicrobiana; Minas frescal; Escherichia coli; cheese; STEC; ExPEC; antimicrobial resistance; Minas frescal